CHARACTERIZATION AND USE OF ISABEL'S GRAPE SEED OIL AFTER THE VINIFICATION PROCESS - Constantini, Mayara Isolde; Nogueira, Maria; Mafi, Suzimar; Soares, Fabiana; Megiolaro, Fernanda; Caliari, Vinicius (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Vitiviniculture has become an important activity for the growth of small farms. In the region of Santa Catarina there are many wineries, which in turn, generate waste after the vinification process (bagasse). With this objective, we evaluated the oil of the grape seed (Vitis labrusca, variety “Isabel”) after the vinification, for possible use in cosmetic. The physical-chemical characterization of the oil of the grape seed was obtained through the analyzes of yield 7.29%; acidity 0.045mg KOH / g; volatile matter 0.64%; peroxide index 6.63 meq O2; density 0.91 g.cm3; pH 5, retraction index 1.47n and saponification 194%. It was verified that the grape seed oil analyzed, obtained values accepted by the current legislation and, therefore, can be used as raw material for new products. Contributing in the reduction of the environmental impact generated by the wineries and with their possible reutilization, generating increase of income to the producer. With the results achieved, we developed a hand cream with different concentrations (1% and 3% oil) and evaluated its organoleptic characteristics (appearance, color, smell and touch), physical-chemical (pH, centrifuge and spreadability), and sensory (absorption, drying, stickiness, spreadability, consistency, sensation: oily, hydration and softness of the skin). Keywords: vinification. Reuse of residues. Grape seed oil. Cosmetic. Financial support: UNOESC. E-mails - may89_05@hotmail.com; vinicius.caliari@unoesc.edu.br